1974
DOI: 10.1159/000130307
|View full text |Cite
|
Sign up to set email alerts
|

Sex-chromosome pairing and male fertility

Abstract: In this paper a hypothesis is presented which relates chromosome pairing and sterility in males. This hypothesis has been formulated on the basis of data from numerous meiotic systems in the male of Drosophila melanogaster, where the sex chromosomes have heterochromatic pairing sites, sites which must interact in order for postmeiotic development to be normal. The predictions of this theory have been tested in three principal situations: (1) in various sex chromosome systems of man, the mouse, voles, and beetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 11 publications
6
104
0
1
Order By: Relevance
“…Miklos (1974) suggested that a saturation of pairing sites is necessary to permit a regular maturation of germ cells. In this context, the extensive synapsis observed in this haploid rye is considered to be nonhomologous and it takes place in order to satisfy pairing requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Miklos (1974) suggested that a saturation of pairing sites is necessary to permit a regular maturation of germ cells. In this context, the extensive synapsis observed in this haploid rye is considered to be nonhomologous and it takes place in order to satisfy pairing requirements.…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible to tell whether the relationship between the two is causative or whether both are influenced by the same genes. If one likes to apply Miklos' (1974) hypothesis regarding spermiogenic arrest one could state that a high chiasma frequency results from enough meiotic pairing sites being occupied. Unoccupied sites, according to the hypothesis, would lead to decondensation of chromatin sometime afterwards.…”
Section: Tablementioning
confidence: 99%
“…A relation between univalence and a breakdown of meiosis has been suggested both for the mouse and for man (Miklos, 1974;Searle, 1974;Chandley et al, 1975). We have investigated this point further by comparing the epididymal sperm count with the counts for translocation-caused univalence and the chiasma counts, using the son-sire pairs of this experiment.…”
Section: Introductionmentioning
confidence: 99%
“…One idea is that MSCI and meiotic silencing by unpaired chromatin exist only as an evolutionary relic of meiotic silencing of unpaired DNA, a host defense mechanism first described in Neurospora crassa (21) with analogies in metazoans such as Caenorhabditis elegans (22). Other ideas suggest that silencing is obligatory for the suppression of recombination between nonhomologous regions of the X and Y (23), or for preventing asynapsed XY regions from triggering the meiotic checkpoint (24).…”
mentioning
confidence: 99%